1983
DOI: 10.1159/000280895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Prostaglandins on Urinary Bladder and Urethra Isolated from the Dog

Abstract: Effects of prostaglandins (PGs) E1; E2 and F on the vesical and urethral smooth muscles of dogs were isometrically investigated in vitro. In vesical smooth muscles, 10––8–10––6 g PGE1/ml produced biphasic responses in the dome preparations; relaxation at 10––8 g/ml and contractions at 10––7–10––6 g/ml. In the trigone preparations, 10––8–10––6 g PGE1/ml caused dose-dependent cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
2
9
0
1
Order By: Relevance
“…thra was slightly contracted by PG F2a but was not affected by PG E2. In this study the rabbit circular ure thral smooth muscle strips showed a dose-dependent relaxation to PG Ei and E2 and a dose-dependent contrac tion to PG F2a, as with those seen in the canine urethra by Mutoh et al [6], Possible reasons for differences between our results and those of Khanna et al [3] are a directional difference of muscle strips (our strips: circular; Khannas': longitudinal), and age differences in the response to PGs [9]. PG Ei, E2 and F2a contracted the rabbit urinary blad der smooth muscle strips in the present study; results which were similar with previous reports [2][3][4][5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…thra was slightly contracted by PG F2a but was not affected by PG E2. In this study the rabbit circular ure thral smooth muscle strips showed a dose-dependent relaxation to PG Ei and E2 and a dose-dependent contrac tion to PG F2a, as with those seen in the canine urethra by Mutoh et al [6], Possible reasons for differences between our results and those of Khanna et al [3] are a directional difference of muscle strips (our strips: circular; Khannas': longitudinal), and age differences in the response to PGs [9]. PG Ei, E2 and F2a contracted the rabbit urinary blad der smooth muscle strips in the present study; results which were similar with previous reports [2][3][4][5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 86%
“…Ghoneim et al [10] reported that PG E2 reduced the canine urethral resistance. Mutoh et al [6] noted that the female canine urethra was relaxed by PG Ei and E2 but was contracted by PG F2a-Khanna et al [3] showed that the rabbit ure-U rina ry bladder Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reports regarding the relaxant effect of PGE 2 in urethral tissues of various species, including hamsters, rabbits, dogs, and humans, PGE 2 has been found to reduce maximum urethral closure pressure in dogs and maximum urethral pressure in humans . However, few studies have noted any marked contribution of EP2 receptor stimulation to reduction in urethral pressure in in vivo studies.…”
Section: Discussionmentioning
confidence: 98%
“…One substance group to be considered is arachidonic acid derivatives from the cyclo-oxygenase system, another being the purine group including adenosine since ATP release is significant in the urothelium [6][9]. E-class prostaglandins are usually contractile on bladder detrusor [10], but inhibitory effects have been reported [11]. Experiments in urothelium-intact and -denuded preparations had shown that cyclo-oxygenase products had a role in regulation of ureteral motility [12].…”
Section: Introductionmentioning
confidence: 99%